Proceedings of the Statistical and Social Inquiry Society of Ireland: twenty-second session 1868/1869, first to third meetings - SSISI (Statistical and Social Inquiry Society of Ireland, 1869)
meeting: The Society met at 35, Molesworth-street, the Eight Hon. William Monsell, Y.P., in
Proceedings 1868/1869
Keywords: 314.15